Kajian Fast Fashion dalam Percepatan Budaya Konsumerisme - Fairus Shinta (JURNAL RUPA, 2018)
The emergence of Industrial capitalism has introduced various forms of commodities which is basicly produced to meet the human needs that subtantly do not change a way of human life, but gradually changed into something entirely run by a social class strategy, and one of them is fashion. Fashion marketing and the creation of fashionable images that made by the capitalists through the media make many people forced, then become bound in following the fashion world. People are made to be obliged to buy the latest or trendy goods with various brands and prices to be regarded as modern humans who follow the times. Until now, the fashion industry has blended with the phenomenon of life acceleration (dromology), where every fashion product is produced and marketed superfastly to the modernists who are the latest lifestyle consumption trend, bringing fashion business to the next stage, Fast Fashion. But on the other hand Fast Fashion development also gives a very significant influence for the society in the culture of consumerism, eliminating awareness of what is appropriate and able to wear, and what is capable and important to have. And closely related in the humanity will empathy towards fellow human beings and also the environment Keywords: Fashion, Fast Fashion, Commodity, Consumerism, Capitalism, Environment.